2016
DOI: 10.1159/000448859
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Embolization Area after Conventional Transcatheter Arterial Chemoembolization for Hepatocellular Carcinoma Using SYNAPSE VINCENT

Abstract: Purpose: Transcatheter arterial chemoembolization (TACE) is one of the most effective therapeutic options for hepatocellular carcinoma (HCC) and it is important to protect residual liver function after treatment as well as the effect. To reduce the liver function deterioration, we evaluated the automatic software to predict the embolization area of TACE in 3 dimensions. Materials and Methods: Automatic prediction software of embolization area was used in chemoembolization of 7 HCCs. Embolization area of chemoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Takamoto et al showed a high correlation between estimated liver volume on preoperative computed tomography and the weight of the resected specimens [ 15 ]. Ogawa et al reported the utility of a 3D volumetric analysis system on computed tomography images to predict the area of the liver that is embolized after transcatheter arterial chemoembolization [ 16 ]. The advantage of 3D volumetric analysis systems compared to 2D ones is that they enable the calculation of the average whole liver signal intensity automatically, from only a small VOI drawn in the liver parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Takamoto et al showed a high correlation between estimated liver volume on preoperative computed tomography and the weight of the resected specimens [ 15 ]. Ogawa et al reported the utility of a 3D volumetric analysis system on computed tomography images to predict the area of the liver that is embolized after transcatheter arterial chemoembolization [ 16 ]. The advantage of 3D volumetric analysis systems compared to 2D ones is that they enable the calculation of the average whole liver signal intensity automatically, from only a small VOI drawn in the liver parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Ogawa et al . reported prediction of the embolization area after conventional TACE for HCC using the SYNAPSE VINCENT system, but there are no previous reports that examined the insertion of a catheter into the main feeding artery with comparison with the distribution of the HCC‐bearing area. In this study, we classified the contrast‐enhanced patterns in four grades and evaluated our results as 47.4% grades 1 and 2 and 52.6% grades 3 and 4 for super‐selective TACE .…”
Section: Discussionmentioning
confidence: 99%
“…This method involved preoperatively obtaining multi‐detector computed tomography images or EOB‐MRI in a Digital Imaging and Communications in Medicine (DICOM) format. The organs were then segmented in each image slice using the image analysis software Analyze® (Mayo Foundation, Rochester, MN, USA) or VINCENT® (Fujifilm, Japan) . Because fewer data were required for real‐time navigation, these data converted the segmented images into surface‐rendering models, which were also used for surgical planning and simulation.…”
Section: Methodsmentioning
confidence: 99%
“…The organs were then segmented in each image slice using the image analysis software Ana-lyze® (Mayo Foundation, Rochester, MN, USA) [12][13][14] or VINCENT® (Fujifilm, Japan). 15,16 Because fewer data were required for real-time navigation, these data converted the segmented images into surfacerendering models, which were also used for surgical planning and simulation. These models sent the data through the hospital information technology network to a special operating room for use with the IG-NS ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%